Bagay a structural-phenomenological discussion of a movement - Vitug, Niccolo Rocamora (2022)
This article discusses the Bagay movement using critical discourse analysis, a structural approach, and the concept of loob or inner life through a phenomenological approach in the context of the Ateneo de Manila in the 1960s, when the university underwent Filipinization. While literature on social movements is useful in understanding Bagay, concepts from the humanities may further enrich it. Starting as a literary movement that forwarded a poetic style characterized by its novel use of imagery and language, Bagay grew into a social movement that influenced changes within the academic landscape of the Ateneo and various aspects of Philippine culture.
Keywords: Social movements; Bagay Movement; Lumbera, Bienvenido L; Tinio, Rolando